Dabigatran trough concentrations in very elderly patients. Issue 4 (25th September 2020) - Gommans, Ellis; Grouls, René J E; Kerkhof, Daan; Houterman, Saskia; Simmers, Tim; Van der Linden, Carolien
Abstract : Objectives: The aim of this observational study was to explore dabigatran concentrations in elderly and very elderly patients in a real-life population. Patients aged >75 years receiving dabigatran have a significantly higher risk of gastrointestinal bleeding compared withthose receiving warfarin. High trough concentrations have an important impact on this bleeding risk. Methods: We measured dabigatran trough concentrations in 75 patients with atrial fibrillation, divided into age categories <75, ≥75 to 84 and ≥85 years. The most important exclusion criteria were use of interacting medication and severe renal failure. We analysed absolute trough concentrations and concentrations normalised for dose. Results: Trough concentrations were considerably higher in the highest age category. Dose-normalised medians were 0.66, 0.83 and 1.20 ng/mL/mg in the <75, ≥75–84 and ≥85 age groups, respectively (p=0.004). Conclusion: Clinicians should be aware of higher dabigatran concentrations in elderly patients despite dose reduction.